La prise de possession par le fiduciaire en vertu d'un acte de fiducie - Cordeau, Michel (Les Cahiers de droit, 1983)
Under the Special Corporate Powers Act of the Province of Quebec, a trustee for bondholders, in the event of failure of the corporation to fulfil the conditions of the trust deed, is empowered to take possession, to administer and to sell the assets on which security was given, for the benefit of the bondholders. However, Quebec law does not specify the duties of the trustee when he exercises his powers and this has resulted in numerous court debates. In the first part of this article, the nature of the security obtained under a trust deed is examined in order to establish the framework within which the powers of the trustee are exercised. The second part of this article examines the duties and powers of the trustee when he takes possession, when he administers and when he disposes of the property of the corporation. The author emphasises the inadequacies in the law of Quebec, particularly as to the definition of the duties and powers of the trustee and to the judicial mechanism enabling the trustee for bondholders to take possession and to sell the assets of the corporation. The resulting difficulty of determining the respective rights and duties of the trustee and the corporation gives rise to ambiguous situations.